Evaluation of the use of Antibiotics Quantitatively and Qualitatively in Pharyngitis Patients at Banda Sakti Public Health Center Lhokseumawe - Yuziani Yuziani; Rizka Sofia; Fely Syah Imara Siregar (Media Farmasi: Jurnal Ilmu Farmasi, 2023)
Pharyngitis is inflammation that occurs in the pharynx and often spreads to surrounding tissues which is one of the causes is a bacterial infection. Antibiotics are the main drug of choice for bacterial infection. Evaluation of the use of antibiotics can be done quantitatively and qualitatively. The importance of evaluating the use of antibiotics in pharyngitis patients can reduce drug side effects and prevent resistance. This study's objective was to evaluate if giving antibiotics to pharyngitis patients at Banda Sakti Public Health Lhokseumawe was appropriate, quantitatively using the Defined Daily Dose (DDD) method and qualitatively using the Gyssens method. This research is descriptive. The sampling technique used purposive sampling with a time-limited sampling method. The result showed that the use of antibiotics quantitatively using the DDD method found the highest total DDD was amoxicillin of 10,35 DDD/1000 patients, while the qualitative evaluation using the gyssens method for amoxicillin was classified as category IIIB because the gift was too short, cefadroxil was classified as category IVB because other antibiotics were safer, ciprofloxacin was classified as category V because it is not indicated. This study concludes that the use of antibiotics quantitatively using the DDD method found the highest total DDD was amoxicillin, while the evaluation of the use of antibiotics qualitatively classified inappropriate.